Foreign portfolio investment and economic growth in Malaysia - Duasa, Jarita; Kassim, Salina (Pakistan Institute of Development Economics, 2009)

(untitled)
This study examines the relationship between foreign portfolio investment (FPI) and Malaysia’s economic performance. In particular, the study analyses the relationship between FPI and real gross domestic product (GDP) using the widely adopted Granger causality test and the more recent Toda and Yamamoto’s (1995) non-causality test to establish the direction of causation between the two variables. Similar method is also applied on the relationship between volatility of FPI and real GDP. Additionally, the study uses an innovation accounting by simulating variance decompositions and impulse response functions for further inferences. Using quarterly data covering the period from 1991 to 2006, the study finds evidence that economic growth causes changes in the FPI and its volatility and not vice versa.. The findings suggest that economic performance is the major pull factor in attracting FPI into the country. Thus, it must be ensured that the Malaysian economy remains on a healthy and sustainable growth path so as to maintain investor confidence in the economy.